2016
DOI: 10.1371/journal.pone.0165767
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Dynamic Propensity Studies for Protein Binding and Drug Design

Abstract: We study the dynamic propensity of the backbone hydrogen bonds of the protein MDM2 (the natural regulator of the tumor suppressor p53) in order to determine its binding properties. This approach is fostered by the observation that certain backbone hydrogen bonds at the p53-binding site exhibit a dynamical propensity in simulations that differs markedly form their state-value (that is, formed/not formed) in the PDB structure of the apo protein. To this end, we conduct a series of hydrogen bond propensity calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 24 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Hydrogen bonds are important contributors for the structure and interaction of protein-protein or ligand-receptor. In the drug design, hydrogen bond is critical to obtain the specificity of the drug to protein target [33][34][35]. In this study, malvidin-3-O-glucoside-caspase-3 interaction showed the number of hydrogen and hydrophobic bond lower than other anthocyanins, but performed the highest binding affinity.…”
Section: Resultsmentioning
confidence: 83%
“…Hydrogen bonds are important contributors for the structure and interaction of protein-protein or ligand-receptor. In the drug design, hydrogen bond is critical to obtain the specificity of the drug to protein target [33][34][35]. In this study, malvidin-3-O-glucoside-caspase-3 interaction showed the number of hydrogen and hydrophobic bond lower than other anthocyanins, but performed the highest binding affinity.…”
Section: Resultsmentioning
confidence: 83%
“…Higher HB counts associated with the 33 -bound complexes could deduce an increase in the stability of the proteins [ 43 , 44 ]. Relatively, reduced average HBs (PknA = 122, PknB = 123) in the unbound proteins could possibly indicate an increase in structural flexibility or instability [ 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely documented that the secondary structure of the protein can be stabilized by H-bonding. H-bonds between a protein and its ligand provide binding affinity and specificity of interaction [ 63 ]. A moderate mean number of H-bonds was exhibited between BEA and 3CLpro-pocket A (1–2), 3CLpro-pocket B (1–3), and S protein (0–4) as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%